Innovation in Digital Information Literacy Learning for Generation Z through the FOSIL Model Perceptions - zahra; Rully Khairul Anwar; Yunus Winoto (Indonesian Values and Character Education Journal, 2025)
The rapid development of digital technology requires Generation Z students to possess not only technical skills but also critical and character-oriented digital information literacy. However, digital learning practices in schools tend to focus primarily on the use of technology, without a systematic inquiry framework to develop information evaluation skills and digital character formation. This study aims to analyze perceptions, readiness, and the potential adaptation of the Framework of Skills for Inquiry Learning (FOSIL) in digital information literacy learning. This research employed a descriptive qualitative approach involving teachers, librarians, and students as research participants. Data were collected through semi structured interviews focusing on digital learning experiences, information-seeking habits, and perspectives on FOSIL implementation. The collected data were analyzed using thematic analysis to identify patterns, meanings, and interrelationships among the findings. The results indicate that although digital learning has been actively implemented, students still tend to rely heavily on search engines and artificial intelligence tools and experience difficulties in evaluating the credibility of information. The FOSIL model is perceived as relevant to the learning characteristics of Generation Z, particularly in the Wonder and Reflect stages; however, its implementation requires adequate facilities, strengthened library support, and teacher competency development. This study concludes that adapting FOSIL has the potential to systematically structure digital inquiry processes while simultaneously strengthening students’ responsibility, academic integrity, and ethical media use. These findings have implications for the development of inquiry and character based digital literacy learning models in secondary education.